Mass loss to the trailing stem of a sediment cloud - Lai, Adrian Chun Hin (2020)
Engineering activities, such as disposal of dredged materials or land reclamation, produce sediment clouds that can be characterized by a descending thermal and a trailing stem resulting from an instantaneous release. The mass loss from the trailing stem during the descent induces turbidity in the water column and this is investigated in this study. The experimental data of trailing stems from previous studies were reanalyzed to derive a relationship between the mass loss to the trailing stem and the sediment release conditions. The normalized trailing stem length and the cumulative mass distribution within the stem were then obtained. Finally, an application of the model to estimate the sediment loss to the ambient during sediment disposal is given.